Rapid loss of plastid ndh genes in slipper orchids (Cypripedioideae, Orchidaceae) - Ringelmann, Victoria E.; Wagner, Natascha D. (Frontiers in Plant Science, 2025)
IntroductionThe eleven plastid ndh genes encode for subunits of the ndh (NAD(P)H dehydrogenase-like) complex, which mediates electron flow in photosystem I. The loss of ndh genes in plants was observed in many different lineages of Viridiplantae. In lineages of Orchidaceae, the loss of ndh genes was often associated with myco-heterotrophy. However, in previous studies on this topic only a few slipper orchids were included. Our study aimed to analyze the loss of ndh genes within Cypripedioideae, a subfamily that is assumed to be fully autotroph. MethodsBased on a comprehensive sampling of 100 published plastomes representing 60% of Cypripedioideae species, the phylogenetic relationships were revealed on three levels. For family and subfamily levels, 57 and 66 plastid genes, respectively, were extracted and concatenated in Geneious, while for the genus-level phylogeny, complete plastomes were used to calculate a maximum likelihood tree. Additionally, divergence time estimates were performed to illuminate the evolutionary timeframe of the gene loss. The prevalence, pseudogenization and loss of ndh genes were assessed and visualized along the phylogenetic trees.ResultsThe results confirmed the four analyzed genera of Cypripedioideae to be monophyletic and could increase the resolution within the genera compared to previous studies. The diversification of the subfamily started at about 30 Ma with genus Paphiopedilum displaying the most recent diversification starting at about 11 Ma and showing most speciation events around 4 Ma. The rapid loss of plastid ndh genes within the subfamily Cypripedioideae, particularly in the genera Mexipedium, Phragmipedium and Paphiopedilum could be illustrated. Furthermore, the results illustrated that Cypripedioideae are in an early stage of plastid degradation.Discussion and conclusionsRecent studies showed that partial myco-heterotrophy (mixotrophy) is far more common in plant lineages than originally assumed. Based on our findings, we suggest that the possibility of a mixotrophic lifestyle within (sub-)tropical slipper orchids should be reevaluated. Further research regarding the reasons behind plastid gene loss in slipper orchids could provide a better understanding of the ecological evolution of Cypripedioideae.